Desmodium molliculum (Kunth) DC., an Andean medicinal plant: DNA barcoding and HPLC fingerprint for species discrimination and evaluation of its pharmacological potential - Peñaherrera, Eugenia; Sarmiento-Pacurucu, Josue; Santos-Ordóñez, Efrén; Kachatryan, Alexandr; Cuzco, Nancy; Vanegas, David; Calle-López, Jessica; Villao-Uzho, Liliana; Heyden, Yvan Vander; Wilches, Isabel; León-Tamariz, Fabián (Frontiers in Plant Science, 2025)
In the Ecuadorian traditional medicine, two species of the Desmodium genus, D. adscendens and D. molliculum, are used interchangeably for the treatment of various ailments, particularly those related to inflammatory processes, wound healing, stomach ulcers and liver disorders. Despite the extensive knowledge and characterization of D. adscendens, there is limited information regarding D. molliculum. This highlights the necessity for the development of analytical tools that facilitate the differentiation between these two species and the characterization of the latter. The tools were developed and evaluated at two distinct levels: genetically, using the DNA barcoding technique, and analytically, using chromatographic fingerprinting. Additionally, the antioxidant potential of the samples was evaluated through the establishment of the RACI index, based on various in vitro evaluation techniques. De novo genetic DNA barcodes were obtained for D. molliculum and the phylogenetic analysis separated them from those obtained from D. adscendens, demonstrating that the trnH-psbA, matK, and ITS1 markers are the most effective for differentiating between the species. Additionally, the antioxidant potential of D. molliculum was found to be higher than that of D. adscendens. The apigenin 8-C-glucoside (vitexin), together with tannic and chlorogenic acids have been pointed by HPLC fingerprinting analysis as responsible for this pharmacological activity.